Implementation of Naïve Bayes Method in Classification of Nutritional Status of Toddlers at Pasar Ujungbatu Sosa Public Health Center - Heri Santoso; A Armansyah; Fitri Handayani Siregar (Sekolah Tinggi Ilmu Komputer (STIKOM) Tunas Bangsa, 2022)
Health is a very important field in human life, there have been many studies or studies conducted in the health sector, for example nutrition problems. Nutrients are needed by humans to live healthy in order to be able to move and carry out daily activities. For the fulfillment of nutrition in toddlers is usually influenced by social and economic factors of the family. Toddlers' bodies need balanced nutrition to be able to grow and develop properly. The results of the SSGI in 2021 the stunting rate nationally decreased by 1.6% per year from 27.7% in 2019 to 24.4% in 2021. The data used in this study was 1114 toddler data. From the results of training and data testing consisting of 5 attributes, namely gender, age, weight, height, and upper arm circumference and there are 4 classes for class division, namely over nutrition, good nutrition, less nutrition and poor nutrition. And it is known that the accuracy by using 10 data samples gets an accuracy value of 80%. Thus, the system built using the Naive Bayes method is considered successful in classifying the nutritional status of children under five